Persistent right aortic arch and aberrant left subclavian artery in a dog - Rodrigues, Gabriel Menezes; Gusmão, Isabella Menezes; Muramoto, Caterina; Quessada, Ana Maria; Belettini, Salviano Tramontim; Maia, Luan Vinicius Tezzei; Machado, Maria Leticia Linhares; Costa-Neto, João Moreira da (Brazilian Journal of Veterinary Research and Animal Science, 2024)
A 1.5-year-old male German Shepherd dog was referred to a Teaching Veterinary Hospital with a chronic history of regurgitation and a previous presumptive diagnosis of megaesophagus. An esophagogram showed partial esophageal dilation, suggesting one vascular ring anomaly. Computed tomography identified a persistent right aortic arch (PRAA) and an aberrant left subclavian artery (ALSA). The patient underwent thoracotomy, ligamentum arteriosum ligation, and debridement of the periesophageal region. The ligation of the ALSA was not carried out because the esophagus was observed to be released entirely during the surgical intervention. Therefore, intervention on the subclavian artery was not necessary. Clinical follow-up occurred on seven, 14, and 30 postoperative days. The dog improved, showing only sporadic regurgitations. Clinical history and complementary exams were essential to establish a diagnosis. The liberation of the esophageal transit during surgery contributed to the decision not to perform the ALSA ligation.